STUDI PERHITUNGAN HTR PEBBLE-BED DENGAN BERBAGAI MODEL KISI KERNEL DAN KISI PEBBLE - Zuhair, Zuhair (Faculty of Mathematics and Natural Science, Universitas Negeri Yogyakarta, 2012)
In pebble-bed reactor core, lattice models can be changed and even varies with the changing position of pebble. This sort of thing can be found mainly in the area near the vessel wall. Lattice model applied also depends on the procedure how the cylindrical vessel filled. Some lattice models such as SC, BCC, FCC, SH and HCP often used in the high temperature reactor to treat kernel randomness in the graphite matrix and pebble fuel in the reactor core. In this paper a series of calculations of the reactor multiplication factor (keff) conducted with various model of kernel and pebble lattices. The effect of lattice combination which implies on neutronics performance of HTR pebble-bed design is analyzed utilizing the Monte Carlo transport code MCNP5 and continuous energy nuclear data library ENDF/B-VI. MCNP5 calculations show consistency with the keff values which ​​are almost the same for all combinations of kernel and pebble lattices, but if observed further appears that the keff value is more dependent on pebble lattice than kernel lattice kernel. Kernel lattice provides only a less significant effect. The results of keff predictions of all lattice combinations conclude that whatever kernel lattice model utilized, the BCC pebble lattice model is better adopted in the calculation of HTR pebble-bed design with UO2, PuO2 and ThO2/UO2 fuel.